Improved traceability process for frozen tilapia waste elimination in cold chain - Xinqing Xiao (Cleaner Engineering and Technology, 2021)
Waste elimination or reduction with quality assurance is one of the core issues in broad range applications of actual frozen tilapia cold chain, and traceability process with more energy efficient and sustainable is most important to guarantee the quality and safety of frozen tilapia in cold chain. The aim of this study is to propose an improved traceability process for frozen tilapia waste elimination in cold chain. The process includes the cold chain temperature monitoring by battery-free sensing and critical quality parameters determination by correlation analysis. The cold chain temperature performance, quality performance, correlation analysis performance, quality evaluation with shelf life prediction performance and improved traceability process evaluation were comprehensively analyzed and discussed. Results indicate that the cold chain temperature fluctuation could be well monitored by battery-free sensing, the total viable count (TVC) and total volatile basic nitrogen (TVBN) could be determined as the critical quality parameters. The predicted shelf life with the TVBN was more accurate than that with the TVC since the absolute relative error of the predicted shelf life with TVC and TVBN were about 11.54% and 7.41%. The proposed improved traceability process could well monitor temperature fluctuation, improve the traceability and transparency, guarantee the quality and safety, and finally eliminate the waste in cold chain. This study could also provide some theoretical methods for the other food waste elimination in cold chain.